1959
DOI: 10.1051/parasite/1959343354
|View full text |Cite
|
Sign up to set email alerts
|

La tératologie des Tiques (fin)

Abstract: Anomalies du scutumHyalomma anatolicum. Pervomaisky 1954.Deux femelles présentent des déformations importantes du scutum : l'une montre une échancrure profonde dans la région postérieure médiane du scutum ; chez l'autre, la partie droite du scutum manque et les yeux sont asymétriques. Asymétrie des stigmatesAmblyomma hebraeum Koch. Mozambique. T. Santos Dias 1947.Trois exemplaires. Les stigmates sont asymétriques et il manque des festons ( fig. 61).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…In addition, atrophy or lack of one spiracle was reported in 11 specimens. Campana-Rouget (1959b) documented several types of spiracular abnormalities (asymmetry) in Amblyomma hebraeum and Amblyomma longirostre. In addition, Kar et al (2015) reported spiracular abnormalities in Hyalomma scupense, H. marginatum and R. turanicus.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, atrophy or lack of one spiracle was reported in 11 specimens. Campana-Rouget (1959b) documented several types of spiracular abnormalities (asymmetry) in Amblyomma hebraeum and Amblyomma longirostre. In addition, Kar et al (2015) reported spiracular abnormalities in Hyalomma scupense, H. marginatum and R. turanicus.…”
Section: Discussionmentioning
confidence: 97%
“…Gynandromorphism is one of the most documented abnormalities in ticks (Labruna et al 2002;Keskin et al 2012;Prusinski et al 2015), but also there are several reports about other types of morphological abnormalities, such as asymmetry, fusion of adanal plates and festoons, atrophy or lack of one or two legs (Campana-Rouget 1959b, Guglielmone et al 1999Dergousoff and Chilton 2007;Kar et al 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Like many other cases, the gynandromorphic specimen of this report contained both male and female parts, and divided equally in the dorsal view [ 4 , 14 ]. The sexual characteristics were typical in male and female side of this specimen.…”
mentioning
confidence: 75%
“…Many adult ticks have been identified by many acarologists to date, but there have been few reports of gynandromorphism in the tick species of H. asiaticum . Only Campana-Rouget [ 14 ] reported gynandromorphic H. asiaticum briefly, but in the language of Russian. Additionally, the gynandromorphic specimen of H. asiaticum in this report contained some other particular morphological features which were not reported before.…”
mentioning
confidence: 99%
“…It would appear that malformations of the nymphs and adults of A. arboreus are frequent. Many different forms of teratological abnormalities induced by regeneration and external factors have been described by Buczek (1994) in adult and larval A. reflexus and A. persicus, and by Campana-Rouget (1959) in nymphs of Ornithodoros parkeri and Ornothodoros turicata. Investigations conducted recently on ixodid ticks of the genus Ixodes (Alekseev & Dubinina 1993;Zharkov, Dubinina, Alekseev & Jensen 2000) have revealed a wide distribution of morphological anomalies (in 10-48 % of ticks in different populations) and their dependence on pollu-tion levels in the environment.…”
Section: Discussionmentioning
confidence: 98%